2014
DOI: 10.1007/s15010-014-0638-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pathogen: a case and review of Raoultella planticola

Abstract: Raoultella planticola has been considered a relatively harmless Gram-negative bacteria, rarely associated with clinical infection. However, in recent years, the frequency at which severe infection by R. planticola and drug-resistant strains are reported in literature has increased. Here, we present one case of acute cholecystitis caused by R. planticola, and review all previously reported cases of the infection in an attempt to identify new trends in biological and clinical features of R. planticola infections. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
5
45
0
1
Order By: Relevance
“…Among these cases only one was, like ours, community-acquired, while the others were nosocomial (Ershadi et al, 2014).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Among these cases only one was, like ours, community-acquired, while the others were nosocomial (Ershadi et al, 2014).…”
Section: Discussionsupporting
confidence: 49%
“…In the cases where the patient did not survive, either blood cultures revealed evidence of polymicrobial infection or Raoultella planticola was found to be multidrug-resistant, due to its carrying the carbapenemresistent bla KPC gene (Ershadi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Raoultella planticola is an emerging pathogen: in a review conducted by Ershadi et al (2014), a total of 17 cases of severe infection (dated from 1984 to 2014) were reported, i.e. six patients with bacteraemia, four patients with infections of the gastrointestinal tract, three patients with skin and soft tissues infections, three patients with pneumoniae and one patient with cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the clinical infection cases and microbiologic facts, Ershadi et al [7] suggested 4 scenarios for the natural infection course of Raoultella planticola:…”
Section: Discussionmentioning
confidence: 99%